Perancangan Sistem Informasi Monitoring Kehadiran Karyawan Berbasis Website - ,; , (Jurnal Mahasiswa Aplikasi Teknologi Komputer dan Informasi (JMApTeKsi), 2025)
PT. Golden Riau Jaya is a company engaged in the sale of electrical and lighting products, with various employee divisions, including those working outside the company's reach. The current fingerprint-based attendance system is deemed ineffective as it often causes long queues and unfairness for employees who arrive on time. Additionally, the company faces challenges in monitoring employee tasks, particularly for those working outside the company, such as sales and debt collectors. This study aims to improve employee performance through the development of a web-based information system designed to support selfie-based attendance with location-based services to record attendance time and location in real-time, minimizing fraud. The system also allows employees to report daily tasks and work durations, with all employee data stored using a MySQL database to ensure organized and efficient data management. The results indicate that this system helps monitor employee attendance, enhances transparency, and provides relevant data for performance evaluation, ultimately improving operational efficiency and supporting more effective management decision-making.